2006
DOI: 10.1093/rpd/ncl479
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of double strand break-containing chromosome domains is not inhibited by inactivation of major repair proteins

Abstract: For efficient repair of DNA double strand breaks (DSBs) cells rely on a process that involves the Mre11/Rad50/Nbs1 complex, which may help to protect non-repaired DNA ends from separating until they can be rejoined by DNA repair proteins. It has been observed that as a secondary effect, this process can lead to unintended clustering of multiple, initially separate, DSB-containing chromosome domains. This work demonstrates that neither inactivation of the major repair proteins XRCC3 and the DNA-dependent protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Live cell experiments with cells stably expressing either GFP-MDC1 or GFP-53BP1 confirmed the transient nature of MDC1 foci formation and the more long-lived nature of 53BP1 assemblies ( Fig 2B). Moreover, and consistent with previous work describing clustering of DNA breaks (Aten et al, 2004;Krawczyk et al, 2006;Neumaier et al, 2012;Roukos et al, 2013;Aymard et al, 2017;Sollazzo et al, 2018), we observed signs of coalescence of 53BP1 compartments over time upon DNA damage ( Fig 3A). Comparing 53BP1 and MDC1 foci intensity and area suggested that this was more pronounced for 53BP1 ( Fig 3A and B, and Appendix Fig S5A).…”
Section: Resultssupporting
confidence: 92%
“…Live cell experiments with cells stably expressing either GFP-MDC1 or GFP-53BP1 confirmed the transient nature of MDC1 foci formation and the more long-lived nature of 53BP1 assemblies ( Fig 2B). Moreover, and consistent with previous work describing clustering of DNA breaks (Aten et al, 2004;Krawczyk et al, 2006;Neumaier et al, 2012;Roukos et al, 2013;Aymard et al, 2017;Sollazzo et al, 2018), we observed signs of coalescence of 53BP1 compartments over time upon DNA damage ( Fig 3A). Comparing 53BP1 and MDC1 foci intensity and area suggested that this was more pronounced for 53BP1 ( Fig 3A and B, and Appendix Fig S5A).…”
Section: Resultssupporting
confidence: 92%
“…These clusters often split and reform, suggesting that they result from random collisions associated with Brownian chromatin motions [21, 25, 37, 66]. However, RIF clusters can also remain merged for an extended period of time [2, 23, 37, 83]. Inelastic collisions leading to clustering suggest the existence of forces that maintain associations between repair sites, likely mediated by bridging proteins.…”
Section: ‘Inelastic Collisions’ Results In the Formation Of Rif Clustementioning
confidence: 99%
“…RIF clustering has been observed in many independent studies [13, 21, 23, 25, 29, 37, 66, 83], and its meaning and consequences remain mostly speculative. One interesting possibility is that RIF clustering could have different functions and consequences in different cell types, cell cycle phases, and chromatin environments.…”
Section: ‘Inelastic Collisions’ Results In the Formation Of Rif Clustementioning
confidence: 99%
“…We next considered the clustering of dysfunctional telomeres as a source of the phenomenon observed. DSBs induced by a variety of treatments have been shown to undergo clustering (Aten et al 2004;Krawczyk et al 2006;Neumaier et al 2012;Cho et al 2014;Mao et al 2016), but the mechanism underlying these associations has not been determined. We argued that if dysfunctional telomeres become clustered, the number of telomeres detected per nucleus should decrease after treatment of the TRF1 F/F TRF2 F/F Lig4 −/− MEFs with Cre.…”
Section: Bp1-dependent Clustering Of Dysfunctional Telomeresmentioning
confidence: 99%